2022
DOI: 10.3389/fimmu.2022.929289
|View full text |Cite
|
Sign up to set email alerts
|

Intimate intertwining of the pathogenesis of hypoxia and systemic sclerosis: A transcriptome integration analysis

Abstract: ObjectivesSystemic sclerosis (SSc) is an autoimmune disease caused by various pathogenic factors, including hypoxia. Hypoxia stimulates the production of the extracellular matrix to promote fibrosis. However, the integrated function and the underlying mechanism of hypoxia in SSc are unclear.MethodsIn the present study, we used Agilent SurePrint G3 Human Gene Expression v3 for the transcriptional sequencing of fibroblasts with and without hypoxia to detect differentially expressed genes (DEGs) in hypoxia. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…HIF-1α/VEGF signaling pathway plays an important role in mediating the effect of hypoxia-induced EndMT, in the skin microvascular remodeling of SSc [159]. By analyzing differential transcriptomic data from fibroblasts with and without hypoxia treatment, He et al identified nine hypoxia-associated hub genes affecting the pentose phosphate pathway, oxidative stress, and lipolysis, which implicated roles of hypoxiamediated-non-fibrosis mechanisms on SSc pathogenesis [160]. In SSc-PAH patients, a cohort study found that the single nucleotide polymorphism of HIF1A gene (rs12434438 SNP) may be associated with severe PAH among SSc patients [161].…”
Section: Hif Pathwaymentioning
confidence: 99%
“…HIF-1α/VEGF signaling pathway plays an important role in mediating the effect of hypoxia-induced EndMT, in the skin microvascular remodeling of SSc [159]. By analyzing differential transcriptomic data from fibroblasts with and without hypoxia treatment, He et al identified nine hypoxia-associated hub genes affecting the pentose phosphate pathway, oxidative stress, and lipolysis, which implicated roles of hypoxiamediated-non-fibrosis mechanisms on SSc pathogenesis [160]. In SSc-PAH patients, a cohort study found that the single nucleotide polymorphism of HIF1A gene (rs12434438 SNP) may be associated with severe PAH among SSc patients [161].…”
Section: Hif Pathwaymentioning
confidence: 99%